Political judicialization and political activism: an approach to Latin America - Feoli V., Marco (2016)
There are things that the judges do that impact on the political sphere, the sphere of those who represent the other state bodies. It has long been accepted that the judges had a different field of proceeding from the other public institutions, but this situation has been changing in the recent years. Indeed, we are witness the persistent dismantling of the idea that the judge is "the mouth of the law", a mere applicator of rules, and this fact has contributed to an internalization of concepts like judicialization of politics or judicial activism. Its scope and the differences between them is the following paper about.